2021
DOI: 10.3390/en14175220
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Ion Battery Operation, Degradation, and Aging Mechanism in Electric Vehicles: An Overview

Abstract: Understanding the aging mechanism for lithium-ion batteries (LiBs) is crucial for optimizing the battery operation in real-life applications. This article gives a systematic description of the LiBs aging in real-life electric vehicle (EV) applications. First, the characteristics of the common EVs and the lithium-ion chemistries used in these applications are described. The battery operation in EVs is then classified into three modes: charging, standby, and driving, which are subsequently described. Finally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 92 publications
0
36
0
Order By: Relevance
“…A direct simulation of such processes, which can take days, months and years of cycling in real time [ 59 , 60 , 61 ], exceeds the computationally accessible time scales by multiple orders of magnitude. We therefore adopt and adjust a recently introduced statistical sampling scheme by Türk et al [ 40 ] to assess possible (inter-)diffusion processes across interfaces in our simulations.…”
Section: Resultsmentioning
confidence: 99%
“…A direct simulation of such processes, which can take days, months and years of cycling in real time [ 59 , 60 , 61 ], exceeds the computationally accessible time scales by multiple orders of magnitude. We therefore adopt and adjust a recently introduced statistical sampling scheme by Türk et al [ 40 ] to assess possible (inter-)diffusion processes across interfaces in our simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Three peaks decrease in the process of aging, which reflects the loss of the active materials (LAM) and loss of lithium inventory (LLI) on the electrode. The DVA method is also commonly applied in the aging mechanism identification [6,42,43]. Ira et al found that lithium-capacity-consuming side reactions were mainly occurring at anodes [23].…”
Section: Open-circuit-voltage (Ocv) Curve-based Analysismentioning
confidence: 99%
“…They used a BaSyTec Cell System to realize the formation and the cycling of coin cells. The cycling method of the cells are constantcurrent-constant-voltage (CCCV) in discharge and constant-current (CC) in discharge The DVA method is also commonly applied in the aging mechanism identification [6,42,43]. Ira et al found that lithium-capacity-consuming side reactions were mainly occurring at anodes [23].…”
Section: Open-circuit-voltage (Ocv) Curve-based Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving the fast-charging goal without negatively impacting the lifetime and safety is a key challenge nowadays in Lithium-ion battery research 1,2 . Compared with the standard constant current-constant voltage (CC-CV) charging protocol, the constant current (CC) charging mode without the CV segment not only significantly shortens the charging time but also effectively prolongs 20% of the battery service life [3][4][5] . Based on the CC charging protocol, a series of optimized charging protocols, such as pulse charging 6 and multistage constant current charging 7 , are designed to extend the battery life further or shorten charging time.…”
Section: Introductionmentioning
confidence: 99%